Experimental Study of The Alternative Analysis of Cross-Section Variety of Half-Circle, Bowl and Isosceles Triangle to Generate Electricity: A Case Study of Pico Hydro-Pelton Turbines in ITATS Surabaya - syamsuri syamsuri; Ahmad Anas Arifin; M Arif Hidayatulloh (Universitas Sultan Ageng Tirtayasa, 2021)
One of the main urgencies of a developing country such as Indonesia is developing energy supply. Under the government regulation, Indonesia thrives the supply of electricity which mainly maintain by fossil fuels such as oil, gas and coal. This energy supply is limited from time to time. To alternate the condition, environment-friendly energy sources need to be developed. One such energy source is Pico hydro with the use of the concept of a hydroelectric power generator. As we know, this type of generator proven only useful in small, remote communities balanced with a small amount of electricity and considerably function with the Pelton turbines. This study focuses to maximize the valve opening of Pelton turbines to give a good distribution system to generate the electricity. The variety of valve opening of 18⁰, 36⁰, 54⁰, 72⁰ and 90⁰ are matched to the variety of cross-section of the half-circle, bowl and Isosceles Triangle. The result of this research is that the greater the valve opening the greater the efficiency system. Type of bowl blade results in greater efficiency of the system than the semicircular and isosceles triangular blade.